Age-related loss of innate immune antimicrobial function of dermal fat is mediated by transforming growth factor beta - Zhang, Ling-juan (Immunity, 2018)
Dermal fibroblasts (dFB) resist infection by locally differentiating into adipocytes and producing the antimicrobial peptide cathelicidin in response to S. aureus. Here we showed that neonatal skin was enriched with adipogenic dFB and immature dermal fat that highly expressed cathelicidin.. The pool of adipogenic and antimicrobial dFB declined after birth, leading to an age-dependent loss of dermal fat and a decrease of adipogenesis and Camp production in response to infection. Transforming growth factor beta (TGFβ) was identified as a key upstream regulator of this process that acted on uncommitted embryonic and adult dFB and inhibited their adipogenic and antimicrobial function. Furthermore, inhibition of the TGFβ receptor restored the adipogenic and antimicrobial function of dFB in culture and increased resistance of adult mice to S. aureus infection. These results provide insight into changes in the skin innate immune system that occur between the perinatal and adult periods of life.